1993
DOI: 10.1159/000110308
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial on the Treatment for Acute Partial Ischemic Stroke with Acupuncture

Abstract: The effectiveness of acupuncture in acute stroke remains largely untested and unproved. A randomized, controlled trial was carried out to study the feasibility of acupuncture in combination with conventional supportive treatment for acute stroke patients. A total of 30 patients, aged 46-74, with the onset of symptoms within 36 h were enrolled into the study after appropriate screening. All patients gave informed consent. Basing on the same supportive treatment, patients were randomly assigned to a treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 6 publications
3
55
1
Order By: Relevance
“…[7][8][9][10] However, randomized controlled trials have yet to show convincing evidence of benefit in acute and subacute ischemic stroke. [11][12][13] In the earlier trials conducted outside China, 2 studies showed that acupuncture can improve motor function and independence in activities of daily living (ADL), 14,15 whereas 2 trials using sham treatment as control did not find evidence of benefit. 16,17 Although, by contrast, many Chinese trials reported positive results, the conclusions were not regarded as robust, as a result of small sample size and methodological weaknesses as follows: the use of outcome measures that were not internationally recognized; unclear methods of randomization and allocation concealment; the lack of long-term follow-up; and publication bias.…”
mentioning
confidence: 99%
“…[7][8][9][10] However, randomized controlled trials have yet to show convincing evidence of benefit in acute and subacute ischemic stroke. [11][12][13] In the earlier trials conducted outside China, 2 studies showed that acupuncture can improve motor function and independence in activities of daily living (ADL), 14,15 whereas 2 trials using sham treatment as control did not find evidence of benefit. 16,17 Although, by contrast, many Chinese trials reported positive results, the conclusions were not regarded as robust, as a result of small sample size and methodological weaknesses as follows: the use of outcome measures that were not internationally recognized; unclear methods of randomization and allocation concealment; the lack of long-term follow-up; and publication bias.…”
mentioning
confidence: 99%
“…10,11 The utility of acupuncture treatment remains under investigation, even with many lines of evidence supporting its use across diseases. Numerous studies [12][13][14][15] support the clinical efficacy of acupuncture in stroke rehabilitation, especially in China; nevertheless, some conflicting evidence exists. 16 Systematic reviews of trials of acupuncture in stroke rehabilitation have been conducted, 13,[17][18][19][20][21] including trials on stroke patients in acute, subacute, or chronic stages.…”
mentioning
confidence: 99%
“…All 12 trials showed that the acupuncture group was better in functional recovery than the control group, although none had sample size calculation or used intention-to-treat analysis. Among the 12 trials, only 1 4 compared the efficacy of acupuncture plus PT and OT with that of PT and OT alone, whereas in the English literature, 10 RCTs were found [5][6][7][8][9][10][11][12][13][14] between 1966 and March 2001, using the same inclusion criteria. Excluding 2 long-term follow-up studies 13,14 of the same sample of previously reported trials, 5,9 2 6,12 of the remaining 8 RCTs reported negative results and 2 7,9 reported positive results in both impairment and disability measures.…”
mentioning
confidence: 99%